Perbedaan Hari Raya Dalam Negara Majemuk Indonesia Perspektif Hukum Islam - Syafa’at, Andi Airiza Rezki; M, Misbahuddin; S, Shuhufi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research discusses how holidays differ in Indonesia. The difference in determining the start of the Qamariah month, especially the start of Ramadan, Shawwal and Zulhijah, is a recurring phenomenon in Indonesia. These differences often cause unrest among Muslims, disrupt the solemnity of worship and even threaten the stability of the brotherhood. Ru'yatul hilal is a practical method to prove whether the new crescent moon (hilal) is visible or not. If in astronomy the celestial objects that are usually rukyat are recommended to be above an angle of 15 degrees, then ru'yatul hilal is done when the moon's irtifa' is still very low, and is done every 29th of Sha'ban or Ramadan regardless of whether it has been ijtima' or not. The science of arithmetic is the equivalent of the science of astronomy, which is a branch of applied astronomy that discusses determining times of worship by calculating the position of the sun and moon relative to the earth. The issue of reckoning and rukyat at the beginning of the month of Qamariah is an important issue because it is related to determining major Muslim holidays, for example the months of Ramadhan, Shawwal and Zulhijah.